The solution of the given equation is y = (6x - 11)/4.
The equation is defined as mathematical statements that have a minimum of two terms containing variables or numbers that are equal.
We have been given that equation as
⇒ 6x - 4y = 11
We have to determine the solution for y.
⇒ 6x - 4y = 11
Rearrange the terms of the above equation and solve for y,
⇒ 4y = 6x - 11
Divided by 4 on both the side of the equation, we get
⇒ y = (6x - 11)/4
Hence, the solution of the given equation is y = (6x - 11)/4.
Learn more about the equation here:
brainly.com/question/10413253
#SPJ1